FORMS OF FINDING URANIUM SATELLITE ELEMENTS IN ALBITITES OF THE UKRAINIAN SHIELD - Fomin Yu.; Demikhov Yu.; Verkhovtsev V.; Dudar T. (Геохімія техногенезу, 2019)
The article deals with the forms of trace elements occurrence that accompany uranium mineralization. They can be both: the concentrators themselves and common rock-forming minerals. The first include the native metals - gold, bismuth, lead; sulfides of Cu, Zn, Pb, Ni, Co; monazite (Th), zircon (Zr, Th). Examples of the second group are feldspar, rubidium, strontium, and lead; aegirine, riebeckite, sphene and vanadium. Trace elements were considered according to the following system: radioactive, siderophilic, chalcophilic, rare and rare earth elements, as well as elements-mineralizers within the studied albitite uranium deposits. Four forms of uranium are found in albitite deposit systems. These are (1) uranium minerals; (2) highly radioactive accessory minerals; (3) uranium scattered in rock and ore-forming miner-als; (4) uranium mobilized (sorbed) by secondary minerals. The highest mobility of metals is recorded in the ground and surface waters, as well as in soils and upper parts of the weathering crust. Uranium turned out to be the most mobile of the radioactive metals (the widest secondary aureole), radium is concentrated closer to primary uranium ores, and thorium associated with monazite is relatively stable. Tak-ing into account geological and geochemical characteristics of albitite deposits, as well as landscape and geochemical features of the Ingulskyi megablock (transition between forest-steppe and steppe zones), the region seems very promising for the formation of surface concentrations of uranium and accompanying elements (V, Cu, Zn, Zn Mo, Pb). All described constituents of ore mass of albitite for-mation deposits, except for directly uranium minerals, can be considered as uranium mining tailings that have been (and will be) accumu-lated. In essence, it is grinded mineral concentrate enriched in uranium and impurities described and placed under conditions of hyper-genic processes favorable for oxidation and decomposition. The removal of metals (in most cases toxic ones) by atmospheric waters into hydrographic network, their subsequent migration into the groundwater system, gradual penetration into soils and biological objects is obviously can be forecasted.